A focus to green synthesis of metal/metal based oxide nanoparticles: Various mechanisms and applications towards ecological approach. (15th November 2021) - Kumar, J. Aravind; Krithiga, T.; Manigandan, S.; Sathish, S.; Renita, A. Annam; Prakash, P.; Prasad, B.S. Naveen; Kumar, T.R. Praveen; Rajasimman, M.; Hosseini-Bandegharaei, A.; Prabu, D.; Crispin, S.
Abstract: Nanomaterial synthesis using a greener route has received massive attention as a sustainable, feasible, reliable, cost-effective, wealthy and environmentally friendly paradigm. Perhaps, synthesis via a greener route is considered as a sophisticated tool to minimize the toxic effects agglomerated with the conventional procedures of synthesis adapted for nanomaterials generally preferable in industry and laboratory. This work outlines the basic processes on the advanced patterns of the eco-friendly and various approaches involved in the green synthesis and its mechanism particularly accounted to metal and metal-based oxides like silver (Ag), gold (Au), zinc oxide (ZnO) and copper oxide (CuO) nanoparticles with the aid of plant extracts. This review article encompasses the essential purpose of biological approaches, green roué for nanoparticle synthesis, the impact of various operating parameters, and solvent-based techniques. The toxicity/stability of nanomaterials and the occluded surface engineering protocols for deriving biocompatibility along with various solvent systems have also been outlined. Various mechanisms involved for green synthesis, merits of greener chemistry and its application in various fields are emphasized. Finally, the prospects of green route strategies for metal/metal oxide nanomaterials synthesis are proposed for further development. The challenges in utilizing the green synthesized metal/metal oxide nanoparticles are discussed. The recommendations of the green chemistry towards the cleaner production are emphasized. Graphical abstract: Image 1 Highlights: This audit features the strategies for green synthesis of metal nanoparticles. The metal oxide nanoparticles have been synthesized effectively by greener route utilizing bio species. The plant extracts have exceptional properties which can be used as reducing agent for stabilization of nanoparticles Future viewpoints and their prospective applications towards environmental applications are recommended.